Moving architectureThe Impact of position movement of architectureon therecipient - Almajedi, Basim Hasan; altaee, Mariam Mohmmed (Iraqi Journal of Architecture and Planning, 2018)
The moveable building is considered to be one of the most recent productions of the era which is related to the concepts of the benefit, beautyand the technique. These concepts have great impact on the movement of society and human being through his awareness to his recent needs that are changing through the time, which effect the role of techniques that related to the humans services through spotlighting the relationship between these effects from one side and the human from the other side to get anew architectural product represented through the moveable building. This product interacts with the humans existance in the society through many factors which can be used communicatively with the society in general.This product affects the human directly becouse it’s a product which has an aesthetic action, functional, and technical. This research illustrates the connection of the moveable pattern elements through its design and the effect of this movement to the recipient; this point illustrats the need of studying the relationship between the moveable product and human. The target of this research is to put a cognitive framework leads to illustrate knowing the moveable building through establishing a theoretical framework which will connect between the movement in the building and its relationship with the recipient,for this reason the problem of the research is ( the absense and deficiency of the existing knowledge about the relationship between the moveable building and the recipient ), after that apply this relationship to a number of particular knowleging indicators, analyse this applicaion, illustrate the relationship between the moveable building and the recipient and finally find conclusions for Research.